THE INFLUENCE OF FAMILY ENVIRONMENT AND SELFEFFICACY ON INTEREST IN BECOMING A STUDENT TEACHER IN THE EDUCATION STUDY PROGRAM, FACULTY OF ECONOMICS, JAKARTA STATE UNIVERSITY 2018 - Larasati, Dinda Putri; Karyaningsih, RR Ponco Dewi; Marsofiyati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of family environment and selfefficacy on the interest in becoming a teacher for students of the Education Study Program, Faculty of Economics, State University of Jakarta batch 2018. This research was conducted for 8 months starting from January 2022 to August 2022. The method used in this study is the method survey. Technique uses Proportional Stratified Random Sampling with a sample of 175 respondents was obtained from the 2018 Faculty of Economics Education Study Program students. The data was collected through distributing questionnaires using a Likert scale. Based on the results of the research conducted, it was found that Family Environment has a positive and significant effect on Interest in Becoming a Teacher. SelfEfficacy has a positive and significant effect on Interest in Becoming a Teacher. According to the research hypothesis.